CFD Modelling of a Helium Cryogenic Pulsating Heat Pipe. Issue 1 (1st May 2022) - Xu, C; Pfotenhuaer, J; Miller, F
Abstract: This paper explores the development of a 3D model using ANSYS Fluent to characterize the two-phase (gas/liquid) flow of helium in a cryogenic pulsating heat pipe. The model includes condensation and evaporation phenomena and uses the VOF model to capture aspects of the two phase flow. Temperature dependent properties were applied for helium in the range of 2.2 K and 20 K. Bubble formation and movement were observed, as well as flow direction at various times in each of the individual pipes. Grid independence tests were performed by plotting the average temperature of different sections. The influence of the number of turns on the performance of PHP is also investigated.